Improved wear resistance of WS2 film by LT-deposited Ti interlayer with ω phase structure. (September 2018) - Gao, Xiaoming; Sun, Jiayi; Fu, Yanlong; Jiang, Dong; Wang, Desheng; Weng, Lijun; Hu, Ming
Abstract: The goal of this paper was to investigate the structural/mechanical properties of arc-ion-plated Ti film deposited at ultralow temperature (166 K, LT-Ti film) and its effect as an interlayer on the wear resistance of sputtered WS2 film. The results revealed that the LT-Ti film mainly exhibited ω-phase structure due to the insufficient mobility of Ti adatoms at LT surface, while the α-phase was predominated in the Ti film deposited at room temperature (RT-Ti film). The LT-Ti film showed a higher hardness than the RT-Ti film as well as the better toughness and film-substrate adhesion on steel substrates. The wear resistance of sputtered WS2 film could be significantly improved by employing the Ti films as its interlayer, especially for the LT-Ti film. Highlights: Ti films were deposited at substrate temperatures of LT (166 K) and RT (300 K). LT-Ti film mainly exhibited the ω phase structure. The α phase was predominated in RT-Ti film. LT-Ti/WS2 double-layer film presented a better wear-resistance.